Analisis Subtipe HIV-1 dan Faktor Penyebarannya pada Penderita HIV di RS. Yowari Kabupaten Jayapura, Papua - Mirna Widiyanti; Semuel Sandi; Holy A. Wibowo (Jurnal Biologi Papua, 2014)
Acquaired immunodeficiency Syndrome (AIDS) is a symptoms caused by infection with Human Immuno-deficiency Virus (HIV). There are two types of HIV genetically distinguished as HIV-1 and HIV-2 subtype. Subtypes of HIV-1 globally have different distribution in state, where geographical factors could affected to the subtype differences. Papua is one of the provinces that have high case of HIV/AIDS. High number of people with HIV/AIDS in Papua caused by new regional area expansion and mobilization of the population in province and district area. This study was aimed to identify the sub type HIV-1 and the risk factors that correlated in the transmission of HIV-1 type. The research study was performed by cross-sectional design. There were 36 HIV patient sample respondent willing to participate in research and they were sign inform consent. Subtype HIV-1 identification was performed by used Nested-PCR, sequencing, and BLAST to found subtype HIV-1. The interview method used a questionnaires to found of  the risk factors  related to subtype HIV-1. The results of research showed that HIV-1 subtype found in people with HIV in Yowari hospital is CRF01_AE subtype (31 respondent) and subtype B ( 5 respondent). Chi-squre and Fisher exact test analysis of risk factors that influence the spread of HIV-1 subtype showed a non significant results. The research study concluded sub-type HIV-1 in patients is CRF01_AE and subtype B and  there were not correlated risk factors with HIV-1 subtype.Key words: HIV/AIDS , type HIV-1 , CRF01_AE , Sub type-B, RS Yowari.